Enhancement of regeneration ratio and thermal durability for regenerated fiber Bragg grating based on pre-annealing treatment and multimaterial fibers / Nurul Asha Mohd Nazal - Nurul Asha , Mohd Nazal (2020)
Regenerated fiber Bragg grating (RFBG) or also known as regenerated grating (RG) is the creation of the temperature resistant grating through thermal erasure of seed grating (SG) followed by a rebirth of new grating in a annealing process. RG has shown to be a promising fiber Bragg grating component for operation under very high ambient temperature condition. Nonetheless, further investigation and improvement are required to better understand its formation mechanism and to enhance its performance. This study aims to enhance the regeneration ratio and thermal durability of the RG based on pre-annealing treatment and multimaterial fiber. In this work, the effect of the pre-annealing treatment by CO2 laser on regenerated grating formulated in few-mode fibers (FMFs) (two-mode and four-mode step-index fibers) is experimentally investigated. In the preparation, the pristine FMFs were first treated with direct CO2 laser annealing followed by a slow cooling procedure to reduce the internal stresses in the fibers before the grating inscription. After the thermal regeneration process, the produced RGs were then subject to a thermal durability test at 1050°C for 10 hours. In the comparison against the results from the RGs formulated in non-treated FMFs, the finding indicates that RGs in treated fibers have a better regeneration ratio and thermal resilience. It is believed that the thermal stress relaxation and structural rearrangement in the fiber glass are the major factors that lead to the lower grating recovery during the state of thermal regeneration process and higher degradation in the grating strength in a longer exposure period. The elimination and reduction of stresses in the fibers by the laser pre-annealing treatment in the earliest stage enables the grating to be formed in a more thermal stable condition, hence, RGs with prolonged lifespan can be produced. In addition, the study of grating regeneration was extended by fabricating RG in the new class of multimaterial fiber. The finding demonstrates that RG fabricated in the multimaterial fiber has exceptional performance with higher regeneration ratio value as compared with other common commercial fibers. The ultrahigh ratio in the regeneration of grating is correlated to the nano-crystallisation phenomenon of multicomponent in the fiber during regeneration process at high temperature. The results in the thesis provide an understanding of the mechanisms that involve during grating regeneration as well as to improve the effectiveness of RG as an extreme temperature sensor.